Neurotropic effects of distilled water real exposed to Kyokushin Karate katas. Neurotropic Resonance: Biophotonic Information Transfer through Kyokushin Karate-Exposed Water - Valeriy Babelyuk; Igor Popovych; Olga Smoleńska; Anna Michalska; Radosław Muszkieta; Magdalena Hagner-Derengowska; Yuriy Dobrovolsky; Galyna Dubkova; Tetyana Korolyshyn; Walery Zukow (Journal of Education, Health and Sport)
Background. Earlier, we showed that placebo intervention (distilled water with false message of Kyokushin Karate katas, KKK, exposure) produces measurable neurotropic effects. This report presents data on neurotropic effects of water actually exposed to KKK.